The Significance of Epidermal Lipid Metabolism in Whole-Body Physiology. (September 2017) - Kruse, Vibeke; Neess, Ditte; Færgeman, Nils J.
Abstract : The skin is the largest sensory organ of the human body. The skin not only prevents loss of water and other components of the body, but also is involved in regulation of body temperature and serves as an essential barrier, protecting mammals from both routine and extreme environments. Given the importance of the skin in temperature regulation, it is surprising that adaptive alterations in skin functions and morphology only vaguely have been associated with systemic physiological responses. Despite that impaired lipid metabolism in the skin often impairs the epidermal permeability barrier and insulation properties of the skin, its role in regulating systemic physiology and metabolism is yet to be recognized. Trends: Lipid metabolism and acyl-chain trafficking must be strictly coordinated to ensure synthesis of structural lipids required for the epidermal barrier and of lipids that are secreted and coat the skin and the fur. Perturbation of ceramide biosynthesis and turnover impairs the epidermal permeability barrier and results in systemic physiologic effects. Cold exposure of the skin is sensed by cold-sensitive thermoreceptors located in the skin, which initiates receptor-mediated neural signaling that ultimately activates thermogenesis in muscle and in brown adipose tissue and increases browning of white adipose tissue. An impaired epidermal permeability barrier has systemic effects on physiology and metabolism including increased calorie intake, energy expenditure, activation of thermogenic mechanisms, increased glucose tolerance, and resistance to diet-induced obesity.